El juego dirigido como estrategia pedagógica para el desarrollo de habilidades creativas en niños de 3 -4 años. - Zapata Romero, Marjorie Teresa (2025)
Directed play has been consolidated as a fundamental pedagogical strategy in early education, especially for the development of creative skills in 3- and 4-year-old children. According to Vygotsky (1978), play is an essential means for learning, as it allows children to explore, experiment and express their creativity in a safe and structured environment. Creative activities in this context should be varied and stimulating. They should encourage imagination, problem solving and collaboration. Examples include role-playing, where children assume different characters, and art activities, such as painting or building with blocks. These activities not only promote creativity, but also develop social and emotional skills, essential at this stage of development (Berk, 2013). These activities not only promote creativity, but also develop social and emotional skills, essential at this stage of development. The purpose of this research is to determine the impact of play on the teaching-learning process of preschool children. This research was framed within a qualitative approach, with a descriptive-analytical review design, oriented to the identification, selection, analysis and interpretation of relevant scientific sources. This article seeks to carry out a literature review on directed play as a pedagogical strategy in the development of creative skills in 3- and 4-year-old children, in which an exhaustive search related to the topic has been carried out through key words, obtaining as a result a variety in the quality of the information, taking into account the most relevant and concrete for the realization of this document.